PEMANFAATAN LIMBAH SAMPAH SEBAGAI MEDI PEMBELAJARAN AGAMA ISLAM PADA ANAK USIA DINI DI TENGAH PANDEMIC COVID-19 - Rohita Rohita; Miranda Nur Alami; Rizqi Maulida (Riau Journal of Empowerment, 2021)
The existence of the co-19 pandemic is the cause of the implementation of large-scale social restrictions (PSBB), which resulted in almost all Indonesian people can only carry out their activities at home. As a result of the high activity being carried out at home, the by-products in the form of garbage also increased a lot. Both organic and inorganic waste, which often cannot be utilized. On the other hand, the educational process that usually occurs in schools now has to move to the house, with the mother acting as a teacher. Of the many stimulation needs that must be obtained by early childhood, religious values become the main thing that needs to be instilled as a foundation for them to be able to live their lives later. The purpose of this activity is to improve the ability of parents to use waste as a medium of Islamic learning in children. The activity was carried out in the South Tangerang area, with 15 participants having pre-school age children. The activity was carried out using the method of presenting material using a zoom cloud meeting, giving video tutorials, presenting the results of the work, and giving assignments. The results of the activity show that there are many media that participants can produce based on waste, especially cardboard and plastic, to be used in Islamic religious learning in early childhood.